Hyperkalemia Mimicking Anteroseptal Myocardial Infarction: a Rare Feature that Confuses Clinicians - Nugraha, Raka Aldy; Husen, Aulia; Muliawan, Hary Sakti; Zamroni, Dian (Jurnal Kardiologi Indonesia, 2025)
In “Hyperkalemia Mimicking Anteroseptal Myocardial Infarction: a Rare Feature that Confuses Clinicians” (Indonesian Journal of Cardiology, 44(1), 28-32. https://doi.org/10.30701/ijc.1297), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1297. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1297